Efektivitas Pelaksanaan Program Bantuan Operasional Sekolah (BOS) Di MTS Al–Badriyah Cisaat - Aam Ammar Halim; Moh. Fikri Dulyani; Robi Mahludin (Bahasa Indonesia, 2024)
This research was conducted because several problems were found in the implementation of the Bantuan Operasional Sekolah (BOS) at MTs Al-Badriyah Cisaat Sukabumi which was not optimal. The purpose of this study was to identify outputs, policies, and procedures in the implementation of the programme. This research used a qualitative approach with descriptive methods, collecting data through observation, interviews, and documentation. Data validation was conducted through triangulation (techniques, sources, and time) and analysed using reduction, data presentation, and conclusion drawing techniques. The informants consisted of 4 people who were selected by purposive sampling and snowball sampling. The results showed that the implementation of the BOS Programme at MTs Al-Badriyah Cisaat was still hampered by human resources and management that was not optimal.